Pengaruh Behavioral Motivation, Pengetahuan Investasi, Modal Investasi Minimum, Dan Preferensi Risiko Terhadap Minat Investasi Mahasiswa Di Pasar Modal - Rita J. D. Atarwaman (IAIN Palopo, 2021)
This study aims to determine the effect of behavioral motivation, investment knowledge, minimum investment capital, and risk preferences on student investment interest in the capital market. The variable of student investment interest is the dependent variable in the study. While the behavioral motivation variables, investment knowledge, minimum investment capital, and risk preferences are independent variables in the study. The object of this research is students from the Faculty of Economics and Business, University of Pattimura. The sampling technique in this study used simple random sampling method, where the sample was determined based on the slovin formula. The research sample was 136 students (one hundred and thirty six students). The research analysis used the SPSS version 26 program analysis tool. The instrument used in this study was a questionnaire distributed via google form. The results showed that the behavioral motivation variables, minimum investment capital, and risk preferences had a significant effect on students' investment interest in the capital market. While the investment knowledge variable has no effect on student investment interest in the capital market.